Dystopia Analysis in Wall-E Movie - Alifia Hamzah; Salsa Solli Nafsika (Cinematology: Journal Anthology of Film and Television Studies, 2021)
Garbage is a problem of mankind from ancient times, starting from the cans that we throw away and every banana peel that we throw is the root of the problem. Wall-E is an animated film by Pixar Animation Studios and released by Disney Pictures on June 27, 2008, and directed by Andrew Stanson who previously directed Finding Nemo. The dystopia in Wall-E shows how the earth is filled with piles of garbage, which decides humanity must evacuate into space. This study uses Symbolic Convergence Theory or Fantasy Theme, to find out the audience's perception of Wall-E movies and what they capture from the audio visual message. In this study the method used was descriptive analysis through a subjective perspective that focused on the pattern of mass communication seen from the audience's perception of the film Wall-E. The data obtained is from the source of interviews with some students of film and television study programs, indonesian educational universities. Most Wall-E audience members argue that, After watching wall-E movies, they end up caring more about trash and its impact on the earth we live in. Keywords — Garbage, Wall-E Film, Audience perception